Early childhood feeding practices and dental caries among Australian preschoolers. Issue 4 (11th February 2020) - Devenish, Gemma; Mukhtar, Aqif; Begley, Andrea; Spencer, A John; Thomson, W Murray; Ha, Diep; Do, Loc; Scott, Jane A
ABSTRACT: Background: Recent reviews have proposed a causal relationship between prolonged breastfeeding and early childhood caries (ECC), but the evidence to date is inconsistent, with few cohort studies and limited investigation of key confounders. Objective: This study aimed to investigate the relationship between dietary practices and early childhood caries in a birth cohort of Australian preschoolers. Methods: Participants underwent a standardized dental examination at 2–3 y of age to determine the prevalence of ECC (based on the presence of decayed, missing, or filled tooth surfaces). Breastfeeding practices were reported at 3, 6, 12, and 24 mo of age. Intakes of free sugars were assessed at 1 and 2 y of age. Multivariable regression models generated prevalence ratios (PR) for the association between ECC and breastfeeding duration, and between ECC and sleep feeding practices at 1 y, controlling for sociodemographic factors and free sugars intake. Results: There was no independent association between breastfeeding beyond 1 y of age and ECC (PR 1.42, 95% CI: 0.85, 2.38), or between breastfeeding to sleep and ECC (PR 1.12, 95% CI: 0.67, 1.88), although the direction of effect was suggestive of an association. The only factors independently associated with ECC were high free sugars intakes (PR 1.97, 95% CI: 1.13, 3.44), and greater socioeconomic disadvantage (PR 2.15, 95% CI: 1.08, 4.28). Most participants who were breastfed at 1 y of age had ceased by 18 mo or 2 y. Conclusions: Breastfeeding practices were not associated with ECC. Given the wide-ranging benefits of breastfeeding, and the low prevalence of sustained breastfeeding in this study and Australia in general, recommendations to limit breastfeeding are unwarranted, and breastfeeding should be promoted in line with global and national recommendations. To reduce the prevalence of early childhood caries, improved efforts are needed to limit foods high in free sugars.